HISTORICAL SIGNIFICANCE OF THE CREATION AND ACTIVITY OF ALISHER NAVOI IN THE SOCIO-ECONOMIC LIFE OF THE TEMURID PERIOD OF THE 15TH CENTURY (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Alisher Navoi, a great figure of world spirituality of the 15th century, was born on the 17th day of Ramadan 844 AH (February 9, 1441 AH) in Herat. The city of Herat was the second capital of the great empire founded by Amir Temur in the first half of the 15th century, and one of the prosperous settlements under the rule of Temur's youngest son, Shahrukh Mirza. The family where Alisher was born had long been close to the Temurid court and had a certain influence in the country. Fate brought Alisher Navoi close to the great and honorable people of his time, made him acquainted with the most influential and influential people. From 1466 to 1468, Alisher spent most of his life in Samarkand. When Sultan Husayn Boykara captured Herat, Alisher Navoi was already a 28-year-old scholar, a well-known poet and an experienced statesman. Despite the disapproval of his friend, Baykara appointed him to the post of minister in February 1472 and gave him the title of "Amiri Kabir" ("Great Emir"). In this position, Navoi used his position for the benefit of the ulus, the improvement of the city and the country, the prosperity of culture, and the triumph of justice, all of which ultimately ensured the stability and prestige of the Sultan Hussein state.